Block Copolymers by Mechanistic Transformation from PROAD to Iniferter Process - Çiftçi, Mustafa; Yagci, Yusuf (Wiley-V C H Verlag Gmbh, 2018)
A facile strategy for synthesizing block copolymers by the combination of two different living polymerization techniques, namely, photoinduced radical oxidation/addition/deactivation (PROAD) and iniferter processes is described. In the first step, PROAD polymerization of isobutyl vinyl ether using bromotriphenylmethane, dimanganese decacarbonyl (Mn-2(CO)(10)), and diphenyliodonium bromide (Ph2I+Br-) is carried out to yield polymers with triphenylmethyl (trityl) end groups. These prepolymers are used as macroiniferters in thermally induced free radical polymerization of vinyl monomers such as methyl methacrylate, tert-butyl acrylate, and styrene, resulting in the formation of corresponding block copolymers free from homopolymers. The precursor polymer and final block copolymers are characterized by H-1 NMR, FT-IR, GPC, and DSC analyses.
Keywords: block copolymers; cationic polymerization; free radical polymerization; iniferters; mechanistic transformation; photoinduced radical oxidation/addition/deactivation